HUBUNGAN STRESS KERJA DENGAN MOTIVASI KERJA DRIVER OJEK ONLINE (GRAB) DI DAERAH ISTIMEWA YOGYAKARTA - Mariska Khairunnisa Fitriana; Michael Yulian Feno (SINERGI : Jurnal Riset Ilmiah, 2026)
Motivation is the main factor driving someone to carry out their activities in a work environment. Conceptually, if an employee (online motorcycle taxi driver) has high motivation in working, the resulting performance will increase. Driver performance can be affected by work stress. Stress can have a negative impact on a person's psychological and biological state, this also occurs for Grab drivers in Yogyakarta. Because the company's motivational efforts are aimed at achieving high work effectiveness in order to achieve predetermined targets. The purpose of this study was to determine the relationship between work stress and work motivation experienced by online motorcycle taxi drivers (Grab), especially in the city of Yogyakarta. The sample in this study were online motorcycle taxi drivers who are members of the Grab Indonesia company, with no age restrictions, officially registered and domiciled in the city of Yogyakarta. The data collection method was a scale of work stress and work motivation. Data analysis using Product Moment correlation technique, The results of the study showed that the F test showed that the F count value of 59.576> F table value (3.15) with a significance value (Sig.) of 0.000 <0.05, thus indicating that work motivation jointly affects work stress. The conclusion of this study is that there is a positive and significant relationship between work stress and the work motivation of Grab online motorcycle taxi drivers in Yogyakarta